2003
DOI: 10.1038/sj.leu.2403004
|View full text |Cite
|
Sign up to set email alerts
|

Defibrotide reduces procoagulant activity and increases fibrinolytic properties of endothelial cells

Abstract: Defibrotide (DF), a polydeoxyribonucleotide with antithrombotic properties, has recently proven effective in patients with severe hepatic veno-occlusive disease (VOD), a life-threatening complication of high-dose chemo/radiotherapy regimens for stem cell transplantation. To understand the mechanism of its beneficial effect, we studied the impact of DF on the expression of tissue factor (TF) and fibrinolytic proteins (PAI-1 and t-PA) on endothelial cells. The in vitro response to DF of two types of human endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
107
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 40 publications
0
107
0
1
Order By: Relevance
“…[7][8][9][10][11] Preclinical data suggest that defibrotide stabilizes endothelial cells by reducing endothelial-cell activation and by protecting endothelial cells from further damage, resulting in the restoration of the thrombo-fibrinolytic balance. [12][13][14][15][16] The primary objective of this phase 3 study was to demonstrate the efficacy of defibrotide 25 mg/kg per day in patients with hepatic VOD/ SOS with MOF. Efficacy was assessed as the primary end point of difference of survival rate at day 1100 post-HSCT between the 2 groups, as well as the secondary end points of difference of complete response (CR) by day 1100 post-HSCT and survival at day 1180 post-HSCT in patients receiving defibrotide vs historical controls.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Preclinical data suggest that defibrotide stabilizes endothelial cells by reducing endothelial-cell activation and by protecting endothelial cells from further damage, resulting in the restoration of the thrombo-fibrinolytic balance. [12][13][14][15][16] The primary objective of this phase 3 study was to demonstrate the efficacy of defibrotide 25 mg/kg per day in patients with hepatic VOD/ SOS with MOF. Efficacy was assessed as the primary end point of difference of survival rate at day 1100 post-HSCT between the 2 groups, as well as the secondary end points of difference of complete response (CR) by day 1100 post-HSCT and survival at day 1180 post-HSCT in patients receiving defibrotide vs historical controls.…”
Section: Introductionmentioning
confidence: 99%
“…DF is a polydisperse mixture of 90% single-stranded polydesoxyribonucleotides with anti-thrombotic, anti-ischemic, and pro-fibrinolytic functions. [1][2][3][4] This mixture is obtained by controlled depolymerization of porcine mucosal DNA and has a mean molecular weight of 16-20 KD. DF is well tolerated and the only therapeutic option in severe hepatic veno-occlusive disease in the course of allogeneic stem cell transplantation (SCT).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical studies, DF exerted a protective effect on injured microvasculature. [14][15][16][17][18] Early retrospective clinical trials of DF in mostly adult patients who fulfilled criteria for severe VOD based on the presence of MOF demonstrated encouraging responses. 19,20 A singlearm cohort study 21 and a prospective randomized trial of mostly adult patients with severe VOD confirmed these findings, clearly indicating efficacy of DF in the treatment of severe VOD.…”
Section: Introductionmentioning
confidence: 99%